Juvenile Recidivism: An Examination of State Measurement Strategies - Casey, William M. (American journal of criminal justice, 2023)
Scholars, practitioners, and policymakers have called for greater uniformity in state juvenile justice systems’ operationalizations of juvenile recidivism. Yet the last censuses of these measurement strategies found that states’ measures varied widely and generally did not conform to recommended best practices. The current study combined reviews of state publications and statutes with communications with juvenile justice agency representatives to create an updated accounting of current measurement practices. Now, nearly one-third of states have adopted the Council of Juvenile Justice Administrators best practices for operationalizing juvenile recidivism. In addition, most states now track youth into the adult criminal justice system. There remains wide variation in the type of system contact assessed and the follow-up period used. Continued improvements in measurement will enable stakeholders to make better comparisons across systems, programs, and states.